FORMULATION AND EVALUATION OF AZELNIDIPINE FAST-DISSOLVING TABLETS - HEMALATHA, BALA; RAMU, ANNE; VIDYADHARA, SURYADEVARA (International Journal of Applied Pharmaceutics, 2025)
Objective: The main aim of the present study was to improve the solubility and rate of dissolution of azelnidipine and thereby increase oral bioavailability. Azelnidipine is a calcium channel blocker that lowers blood pressure by relaxing blood vessels and relieving pressure on them. Azelnidipine is a Biopharmaceutics Classification System (BCS) class II drug with low bioavailability. Methods: The present study involves the preparation and evaluation of solid dispersion of azelnidipine by physical mixing, fusion and solvent evaporation method using polyethylene glycol 6000 (PEG 6000) as a carrier. The prepared solid dispersions were evaluated for various parameters like angle of repose, carr’s index, particle size, drug content, Scanning Electron Microscopy (SEM) analysis, Differential Scanning Calorimetry (DSC), X-ray diffraction (XRD) and in vitro dissolution studies. As part of the project, Microcrystalline Cellulose-Polyethylene Glycol (MCC-PEG) Conjugate, a novel superdisintegrant, was developed. Results: Solid dispersions prepared by fusion (AF 6) in a drug-to-polymer ratio of 1:3 released 99.40% of the drug more quickly than pure drug and other dispersions. The optimized solid dispersion (AF6) was used to prepare fast-dissolving tablets of azelnidipine. In comparison to commercially available and alternative tablet formulations, the study suggests that azelnidipine tablets (AT 13), made with 5% microcrystalline cellulose-polyethylene glycol conjugate as a super disintegrant, exhibited rapid drug release of 99.92% in 15 min. The drug was released in the following order: MCC-PEG Conjugate>Crospovidone>Croscarmellose sodium>Sodium starch glycolate in all tablet preparations containing super disintegrants. Conclusion: It can be inferred that MCC-PEG conjugate is an efficient super disintegrant by comparing its results with those of available commercial super disintegrants and caused the drug azelnidipine to release rapidly from fast-dissolving tablets.